Challenges of Monitoring Food and Nutrition Security in Rural Areas Using Longitudinal Methods: Experiences from the Rufiji Sentinel Food Security and Nutrition Monitoring (FSNM) Study, Tanzania - Ashimogo, G.; Mwageni, E.; Mdoe, N.; Kayunze, K.; Mwakalobo, A. (Tanzania Journal for Population studies and Development, 2009)
This paper gives an empirical account of the challenges of monitoring food and nutrition security in rural areas using panel data, and proposes some corrective measures against most common problems. The presentation uses the case of Rufiji Sentinel Food Security and Nutrition Monitoring (FSNM) study, whose objective is to generate information on food security and nutritional status. An important lesson from the research is that using the iterative survey process that involves taking precautionary measures during planning, as well as periodic modifications of tools and methods for data collection, can generally increase the accuracy of the collected data and the validity of conclusions derived from them. This means that researchers must ensure that sufficient enumerator training, supervision, and quality control mechanisms are in place both before and during data collection. All these have implications for capacity building for planning and implementation of data collection in developing countries.